Isolated astasia manifested by acute infarct of the anterior corpus callosum and cingulate gyrus. Issue 4 (April 2015) - Zhang, Jian; Xing, Shihui; Li, Jingjing; Chen, Li; Chen, Hongbing; Dang, Chao; Liu, Gang; Li, Chuo; Zeng, Jinsheng
Abstract: Astasia, the inability to stand and walk, in the absence of weakness or ataxia, is uncommon and unique. This syndrome is easy to misdiagnose as vestibulocerebellar disease. We report a patient with anterior callosal and cingulate infarction presenting as isolated astasia. A 65-year-old hypertensive man was admitted to our hospital with marked truncal instability. On neurological examination, he was unable to stand and walk independently. When asked to stand up from a sitting position, he had to grasp something nearby to propel himself upwards, and could not use his axial muscles. He collapsed when support was withdrawn. The patient showed no signs of amnesia, aphasia, apraxia or hemiasomatognosia. Diffusion weighted imaging at 3 days after onset demonstrated an acute infarct in the anterior part of the right-sided corpus callosum and cingulate gyrus. Magnetic resonance angiography revealed an occlusion of the right anterior cerebral artery. We discuss the possible mechanisms of astasia due to anterior callosal and cingulate infarction.